A stop-loss risk index - Wei, Wang; Yatracos, Yannis G.; Wei, Wang (My University, 2004)
An index related with the Dutch premium calculation principle [Insur.: Math. Econ. 11 (1992) 129] and the tail conditional expectation [Math. Finance 9 (1999) 203] is proposed to measure the right-tail insurance risk. The index agrees with pure-tail ordering, is superadditive for comonotonic losses and is compared in examples with Wang's [North American Actuarial Journal 2 (1998) 88] index.
Keywords: Risk (Insurance); Mathematics